PENGARUH PROFITABILITAS, CAPITAL INTENCITY DAN NILAI PERUSAHAAN TERHADAP TAX AVOIDANCE (STUDI PADA PERUSAHAAN TERINDEKS LQ-45 DI BURSA EFEK INDONESIA) - Nurhayati, Netty; Harnida, Muthia; Lesmanawati, Dewi; Khairunnisa, Siti; Ariyanti, Hesti (JURNAL KINDAI, 2025)
The objective of this study is to analyze the effect of profitability, capital intensity, and firm value on tax avoidance. The research population consists of 66 companies included in the LQ-45 Index listed on the Indonesia Stock Exchange during the 2022–2024 period. Based on the sampling criteria, 19 companies were selected, resulting in a total of 57 observations. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26 to examine the relationships among the research variables. Profitability is measured using Return on Assets (ROA), capital intensity is assessed through the Capital Intensity Ratio, firm value is measured using Price to Book Value (PBV), and tax avoidance is proxied by the Cash Effective Tax Rate (CETR). The empirical results indicate that capital intensity has a significant partial effect on tax avoidance, while profitability and firm value do not show a significant effect. However, simultaneously, profitability, capital intensity, and firm value are proven to jointly influence tax avoidance. Keywords: profitability, capital intencity, firm value, tax avoidance, agency theory